Pengalaman Pembelajaran Informal Dalam Kalangan Sukarelawan Mycorps, Kuala Lumpur: [Informal Learning Experiences Among MyCorps Volunteers, Kuala Lumpur] (Sains Humanika, 2021)
The study aimed to identify informal learning experiences among MYCORPS volunteers using qualitative methods through semi-structured interviews and using snowball sampling methods. The three objectives of the study were (i) to know the informal learning experiences experienced by the MYCORPS volunteers, (ii) to identify the factors that contributed to the informal learning experiences experienced by the MYCORPS volunteers and (iii) to know the impact of the informal learning experiences experienced by the MYCORPS volunteers. The data obtained were analyzed using thematic analysis method. The informal learning experience is divided into two, soft skills and real skills. The contributing factors to the informal learning experience are learning strategies, outsiders and team members which affects the knowledge, skills and attitudes of volunteers. The chosen phenomenological approach is to understand a phenomenon. The results show that informal learning is experienced through these factors and affects knowledge, skills and attitudes. The study implicates adult learning practitioners, theories used and also the volunteers.
Keywords: Experiences, informal learning, volunteers, adult learning, self-directed learning